Public Debt Management and Bailouts - Becker, Torbjorn (IMF Working Papers; Working Paper ;, 1999)
This paper addresses how public debt should be managed to reduce the cost of private sector bailouts. It uses a tax smoothing model to show that bailouts affect the timing of government deficits and surpluses as well as the composition of public debt. In general, public debt managers will have to monitor the private sector's leverage and portfolio composition in order to design the tax smoothing policy. This contrasts with Ricardian models where households monitor the government's debt. The moral hazard aspect of defaults is also shown to be important in determining an optimal government debt strategy.